Severe and rapidly-progressive Lafora disease associated with NHLRC1 mutation: a case report. (2nd December 2017) - Casciato, Sara; Gambardella, Stefano; Mascia, Addolorata; Quarato, Pier Paolo; D'Aniello, Alfredo; Ackurina, Yana; Albano, Veronica; Fornai, Francesco; Scala, Simona; Di Gennaro, Giancarlo
ABSTRACT: Lafora disease (LD), also known as progressive myoclonic epilepsy-2 (EPM2), is a rare, fatal autosomal recessive disorder typically starting during adolescence in otherwise neurologically normal individuals. It is clinically characterized by insidious of progressive neurological features including seizures, action myoclonus, visual hallucination, ataxia and dementia. Mutations in the laforin ( EPM2A ) gene on chromosome 6q24 or in the malin gene ( NHLRC1 ) on chromosome 6p22 are responsible of LD phenotype. Diagnostic workup includes genetic analysis as well as axillary skin biopsy with evidence of typical periodic acid-Schiff (PAS)-positive polyglucosan inclusion bodies (Lafora bodies) in the apocrine glands and/or in the eccrine duct. Usually, genotype–phenotype correlations do not reveal substantial differences between patients carrying EPM2A and NHLRC1 mutations, but a few specific NHLRC1 mutations appear to correlate with a late onset and slow progressing LD. We report a case of LD due to compound heterozygote NHLRC1 mutation in an adolescent presenting with severe and atypical electro-clinical features, mimicking an autoimmune encephalopathy, and a rapidly progressive clinical course.